To determine which system has the point (4, -3) as a solution, we can substitute \(x = 4\) and \(y = -3\) into each equation in the proposed systems and see if both equations are satisfied.
Let's check each system one by one:
-
System:
- \(7x - 9y = 55\)
- \(3x + 9y = -15\)
For \(7x - 9y = 55\): \[ 7(4) - 9(-3) = 28 + 27 = 55 \quad \text{(True)} \]
For \(3x + 9y = -15\): \[ 3(4) + 9(-3) = 12 - 27 = -15 \quad \text{(True)} \] Both equations are satisfied.
-
System:
- \(7x + 9y = 55\)
- \(3x + 9y = -15\)
For \(7x + 9y = 55\): \[ 7(4) + 9(-3) = 28 - 27 = 1 \quad \text{(False)} \]
Since one equation is false, we can skip checking the second.
-
System:
- \(7x + 9y = 55\)
- \(3x - 9y = -15\)
For \(7x + 9y = 55\): \[ 7(4) + 9(-3) = 28 - 27 = 1 \quad \text{(False)} \]
Since one equation is false, we can skip checking the second.
-
System:
- \(7x - 9y = 55\)
- \(3x - 9y = -15\)
For \(7x - 9y = 55\) (this one we already checked): \[ 7(4) - 9(-3) = 55 \quad \text{(True)} \]
For \(3x - 9y = -15\): \[ 3(4) - 9(-3) = 12 + 27 = 39 \quad \text{(False)} \]
Since one equation is false, we can skip checking the second.
-
System:
- \(7x + 9y = 55\)
- \(3x - 9y = -15\)
For \(7x + 9y = 55\): \[ 7(4) + 9(-3) = 28 - 27 = 1 \quad \text{(False)} \]
Since one equation is false, we can skip checking the second.
From our examination, the only system that has (4, -3) as a solution is:
7x - 9y = 55
3x + 9y = -15